“Biografi Garam” Etnografi Masyarakat Madura pada Tubuh Teater - Moh. Wail (PANTUN, 2019)
The ethnography research toward the body of Madura people is the beginning of creative process which is transformed into the form of body theatre. The methodology of creativity applied is Tubuh Kata Tubuh Tony Broer, based on ethnography research which gradually investigates the emic and etic of Madura people’s body. The basic assumption of this idea is the concept of Folk Body which suggests that theatre body is able to provide information related to some specific communities through inherited body. The biography of salt body reveals the emic of the body of salt society in Madura. Meanwhile the ethnographic research is used as an approach to obtain the most authentic feature toward behavior, character, attitude, as well as the dressing style of Madura community. Pinggir Papas Village is the main focus of this research due to the high consistency of salt farmer activity. It is a village from which salt came first in Madura. Salt is the iconic of subculture landscape. Body theatre based on this folk highlights body culture of Madura people through the intercourse of folklore media, salt farmer activity and madura songs. Those issues become starting point of the exploration of body intercourse in theatre entitled “Salt Biography”.Keywords: Body Theatre, Ethnography Study, South Madura People, Folklore